Ophiolites Debris In The Aveto Unit (Trebbia Valley, Northern Apennines, Italy): A Record Of The Early Oligocene Apenninic Foredeep? - Catanzariti, Rita; Cerrina Feroni, Andrea; Marroni, Michele; Ottria, Giuseppe; Pandolfi, Luca (Ofioliti, 2003)
In the Northern Apennines, the Aveto succession, belonging to the Subligurian domain, sedimented during the Early Oligocene. This time represents a main step in the Alps-Apennines evolution characterized by several geodynamic events such as the Voltri Group exhumation or the development of the Calk-alcaline volcanism The Aveto succession represents a complex depositional system outcropping in the Northern Apennines located, in the palinspastic reconstructions, between the Mesoalpine belt and the Tuscan Domain. The occurrence of andesitic debris in the Aveto succession can be considered a fondamental tool to understand the geodynamic processes that occurred in the Alps-Apennines linkage area. The Aveto succession is characterized by an almost 500m thick turbiditic sequence (the so-called Aveto Formation) characterized by andesitic-bearing coarse grained arenites and conglomerates. The age of this succession has been determined using Nannofossils assemblage that indicates the biozone MNP23 (Early Oligocene). An age of 32ma (Early Oligocene) has been also provided by radiometric datings on the andesitic clasts. Up to now the basement and the top of the Aveto succession have never been recognized because of pervasive deformations related to the the thrusting of the Liguride units onto the Subligurian and Tuscan ones. New biostratigraphic and field data, derived from the new 1:50.000 italian mapping project, have evidenced, the presence of a new stratigraphic unit at the top of Aveto succession cropping out in the Trebbia Valley. This unit is characterized by a sudden change in the sedimentary facies with development of choesive debris flow characterized by the occurence of ophiolitic fragments.The ophiolitic debris is made up of serpentinized peridotites, basalts, radiolarites and limestones of Late Cretaceous-Paleocene age. According to theirs age, petrographic features and absence of metamorphism, these clast can be related to a typical Liguride succession that characterize the tectonic units above the Aveto unit (e.g. Vico, Ottone, Gottero and Antola units). Nannofossils data indicate an Early Oligocene age (MNP23) for the marls associate with the debris flow deposits. The ophiolitic fragments recognized in the debris flow deposits at the top of the Aveto succession indicate that the sedimentation in the Aveto-Subligurian basin has been stopped by the emplacement of the Liguride Units during the Early Oligocene (MNP23). This type of tectono-sedimentary evolution is typical of the chain-foredeep system of the Northern Apennines, where the foredeep sedimentation was interrupted by the emplacement of tectonic units derived from the orogenic belt. Differently from the previuos reconstructions, where the Macigno Formation.(Late Oligocene -Early Miocene) was regarded as first and oldest foredeep deposit, the collected data indicate that the Aveto-Subligurian basin can be regarded as a true Apennine foredeep of Early Oligocene age.